Polymer stabilizer, anti-freezing solution for coal and preparation method of anti-freezing solution

By combining polymer stabilizer with nanocellulose complexes, urea and sodium salt complexes, high stability and low corrosion antifreeze for coal are prepared, which solves the unstable and corrosive performance of the existing antifreeze. The high problem has achieved the improvement of the stability of freezing point and viscosity and economic benefits.

CN119119335APending Publication Date: 2024-12-13INNER MONGOLIA BORAN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411249779.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The antifreeze used by existing coal shipping units is unstable, which can easily lead to lower viscosity, increased freezing point, and high chlorine and calcium content, resulting in negative impact on downstream chemical coal, including deterioration of slurry fluidity and gasification There are problems such as rising furnace wall temperature, increasing coal slurry viscosity, increasing economic costs and corroding metal pipelines.

Method used

Polymer stabilizers are used to combine nanocellulose complexes, urea and sodium salt complexes to prepare freezing points between -50℃ and -60℃, chlorine content ≤80mg/kg, and calcium content ≤5%. The antifreeze for coal is formed by the preparation method of polymer stabilizer and the proportion of components to optimize the antifreeze for high stability and low corrosion.

Benefits of technology

The viscosity and freezing point stability is achieved, the impact on downstream chemical coal is reduced, transportation losses and economic costs are reduced, frozen coal and corrosion problems are avoided, and export coal standards are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119335A_ABST
    Figure CN119119335A_ABST
Patent Text Reader

Abstract

The present invention relates to a polymer stabilizer, a coal anti-freezing solution and a preparation method thereof, and relates to the technical field of anti-freezing solutions, the coal anti-freezing solution comprises the following components by weight: 1%-20% of a polymer stabilizer, 0.1%-5% of a nano cellulose compound, 35%-55% of a urea and sodium salt compound, 0.8%-5% of a pH regulator, and the balance of water. The polymer stabilizer provided by the invention is further applied to the anti-freezing solution for coal, and is matched with the nano-cellulose compound, the urea, the sodium salt compound and other components for use, so that the anti-freezing solution for coal with the freezing point of-50 DEG C to-60 DEG C, the chlorine content of less than or equal to 80mg / kg, the calcium content of less than or equal to 5% and the viscosity and freezing point stability of more than or equal to 30 days is prepared, and the defects in the prior art are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antifreeze liquid, and in particular to a polymer stabilizer, an antifreeze liquid for coal and a preparation method thereof. Background Art

[0002] At present, the antifreeze commonly used by coal shipping units at all levels is made of calcium chloride dihydrate aqueous solution with thickener added. Although its viscosity and freezing point indicators meet the requirements of industry standard TB / T 3208-2023, the performance of this antifreeze is greatly affected by the moisture content in the coal, resulting in extremely poor viscosity and freezing point stability. The viscosity in the system is easy to decrease, and the freezing point is easy to increase, making it difficult to maintain and preserve for a long time. In addition, the chlorine and calcium content of this antifreeze is extremely high, and its corrosiveness cannot meet the relevant standards.

[0003] Affected by the dual requirements of export coal standards and downstream chemical coal requirements, the use of this antifreeze sprayed on commercial coal will lead to an increase in the chloride and calcium ion content in the commercial coal. These ions exist in ionic state after dissolving in water, which will inevitably have a series of negative effects on downstream chemical coal, as follows:

[0004] 1. The fluidity of the slurry becomes worse: the addition of calcium chloride antifreeze causes the free calcium ions to react with the additives to generate a large amount of calcium-containing compounds, thereby increasing the calcium hardness of the water in the water-coal slurry.

[0005] 2. The temperature of the gasifier wall rises and production fluctuates: When the chemical raw material coal sprayed with antifreeze is gasified, the temperature of the gasifier wall may rise abnormally. For example, the temperature of the furnace wall of furnace A is as high as 355°C, and nitrogen needs to be purged urgently to reduce the furnace temperature. Subsequent monitoring also found that the temperature of furnaces A and B randomly exceeded 290°C in many places, which affected the service life of refractory bricks. At the same time, due to the spraying of chlorine-containing antifreeze, the pressure difference of the gasifier burner and the composition of the process gas are prone to fluctuations, the pressure difference at the slag mouth becomes larger, and the slag mouth has wire drawing and slag blocking.

[0006] 3. Coal slurry viscosity increases and gasification is insufficient: Calcium ions in chlorine-containing antifreeze easily react with other minerals in coal (such as aluminum ions, silicon ions, etc.) to form calcium aluminate (Ca(AlO 2 ) 2 ) and calcite (5CaO·2SiO 2 ·H 2 O) and other minerals, which will lead to poor ash fusibility during coal gasification. If the furnace temperature is higher than 1400℃ for a long time, the service life of the gasifier will be shortened.

[0007] 4. Increased economic costs: In order to reduce the viscosity of water-coal slurry to a reasonable range for a good gasification reaction, it is necessary to increase the amount of additives used, which results in an increase in production costs.

[0008] 5. Corrosion of metal pipes and structures: The increase of free chloride ions in the antifreeze will react with hydrogen in water during the high-temperature gasification process to form hydrogen chloride (HCl). Hydrogen chloride is a colorless gas with a pungent odor. Its aqueous solution is commonly known as hydrochloric acid, which is corrosive to metal pipes and structures. Summary of the invention

[0009] In order to solve the above problems, the present invention provides a polymer stabilizer, an antifreeze liquid for coal and a preparation method thereof.

[0010] In a first aspect, the present invention provides a polymer stabilizer, wherein the preparation method of the polymer stabilizer comprises the following steps:

[0011] Mixing water, an emulsifier, vinyl acetate accounting for 1 / 6 to 1 / 4 of the weight of the total vinyl acetate, and an initiator accounting for 1 / 6 to 1 / 4 of the weight of the total initiator, and then stirring and heating to perform a prepolymerization reaction to obtain a first reaction system;

[0012] Add the remaining vinyl acetate and the remaining initiator dropwise to the first reaction system, and continue to stir and react under heat preservation after the addition is completed to obtain a second reaction system;

[0013] Adding glycerol and alkylphenol polyoxyethylene ether into the second reaction system to carry out polymerization reaction to obtain a third reaction system;

[0014] The third reaction system is cooled to room temperature to obtain the polymer stabilizer.

[0015] Furthermore, the weight ratio of the water, the emulsifier, the vinyl acetate, the initiator, the glycerol and the alkylphenol polyoxyethylene ether is (58-65):(0.5-1.8):(30-45):(0.02-0.09):(0.3-2):(0.3-2); the emulsifier includes sodium lauryl sulfate and alkylphenol polyoxyethylene ether; the initiator includes ammonium persulfate; the alkylphenol polyoxyethylene ether includes at least one of alkylphenol polyoxyethylene ether OP-15 and alkylphenol polyoxyethylene ether OP-10.

[0016] Furthermore, the working condition parameters of the prepolymerization reaction include: temperature of 80-90°C, time of 20-40 minutes; the working condition parameters of the heat preservation and stirring reaction include: temperature of 80-90°C, time of 50-70 minutes; the working condition parameters of the polymerization reaction include: temperature of 80-90°C, time of 50-70 minutes; the cooling temperature is 45-55°C.

[0017] In a second aspect, the present invention provides an antifreeze solution for coal, which comprises the following components in terms of weight percentage:

[0018] 1% to 20% of the polymer stabilizer described in any one of the first aspects, 0.1% to 5% of the nanocellulose compound, 35% to 55% of the urea and sodium salt compound, 0.8% to 5% of the pH regulator, and the balance is water.

[0019] Furthermore, the antifreeze solution for coal comprises the following components in percentage by weight:

[0020] 9% polymer stabilizer, 0.5% nanocellulose compound, 50% urea and sodium salt compound, 3% pH adjuster, and the balance is water.

[0021] Furthermore, the nanocellulose compound is obtained by compounding nanocellulose and nanoxanthan gum; the weight ratio of the nanocellulose to the nanoxanthan gum is 1:(1-3.5).

[0022] Furthermore, the urea and sodium salt compound is formed by compounding urea and sodium salt in a weight ratio of (15-30):(65-85); the sodium salt includes at least one of sodium carbonate, sodium acetate, sodium formate, sodium nitrite, sodium thiosulfate, sodium persulfate, sodium nitrate, and sodium silicate; and the pH adjuster includes triethanolamine.

[0023] Furthermore, the performance index parameters of the coal antifreeze liquid include: freezing point: -50°C to -60°C, chlorine content: ≤80mg / kg, calcium content: ≤5wt%, viscosity at 20°C: 30 to 60mPa·s, pH value: 6.5 to 9.5.

[0024] In a third aspect, the present invention provides a method for preparing the antifreeze solution for coal according to any one of the second aspects, the preparation method comprising the following steps:

[0025] The water, urea and sodium salt compound are stirred and mixed, and then the nanocellulose mixture is added and stirred and mixed to obtain a first mixture;

[0026] The remaining components in the antifreeze liquid for coal are added to the first mixed material, and the mixture is stirred and mixed to obtain the antifreeze liquid for coal.

[0027] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:

[0028] The embodiment of the present invention provides a polymer stabilizer, an antifreeze solution for coal and a preparation method thereof. The present invention provides a polymer stabilizer and further applies it to the antifreeze solution for coal, and uses it in combination with components such as a nanocellulose compound, urea and a sodium salt compound to prepare an antifreeze solution for coal with a freezing point of -50°C to -60°C, a chlorine content of ≤80mg / kg, a calcium content of ≤5%, and a viscosity and freezing point stability of ≥30 days, which makes up for the deficiencies of the prior art. Specifically:

[0029] 1) The antifreeze for coal of the present invention is prepared by stirring a polymer stabilizer, a nanocellulose mixture, a urea and sodium salt compound, and a pH adjuster. It is sprayed onto the wall of the carriage and the surface of the coal body through a fixed or mobile spraying device. Due to its high adsorption and antifreeze stability, it is adsorbed on the surface of the box body and can well isolate the moisture contained in the adjacent coal, thereby preventing the coal from sticking to the wall of the carriage, freezing the car, and incomplete unloading. In the practical test of the application of coal transport special trains, the application of antifreeze for coal completely solved the problems of serious freezing of coal on the wall and bottom of the carriage, incomplete coal unloading, serious tonnage reduction, and serious waste. The export coal inspection also met the export standards, with a chlorine content of ≤80mg / kg, and a low chlorine content.

[0030] 2) The present invention adds a nanocellulose mixture, which can be stably dispersed in water and form a stable spatial grid structure due to its rich surface active hydroxyl groups, high aspect ratio, small size, good thermal stability and large surface charge, and has good hydrophilicity and viscosity-increasing properties.

[0031] 3) The present invention uses a polymer stabilizer, which can be combined with urea, sodium salts and nanocellulose to produce a good synergistic effect, resulting in a low freezing point and high viscosity. At the same time, it can also inhibit the growth of microorganisms in the system, so that the freezing point and viscosity stability of the entire liquid phase system are greatly improved, and the influence of the environment and the moisture content in the coal can be basically ignored.

[0032] 4) The antifreeze liquid for coal provided by the present invention has a low freezing point and high stability, which can reach -50°C to -60°C, and has a good antifreeze effect, especially being less affected by the moisture content in the coal.

[0033] 5) The antifreeze for coal provided by the present invention has strong adsorption to the carriage wall, and the viscosity reaches 30-60 mPa·s (20°C). It can form an effective adsorption film on the train carriage wall to prevent the moisture in the coal from contacting the carriage wall, thus avoiding sticking or freezing accidents.

[0034] 6) The antifreeze for coal provided by the present invention is non-corrosive and does not corrode metals such as train cars and accessories, pipes, and rubber; the chlorine content is extremely low, chlorine content ≤80 mg / kg, and does not pollute the environment; the calcium content is ≤5%, which greatly reduces the impact on downstream chemical coal. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0037] Figure 1 A schematic flow chart of a method for preparing a polymer stabilizer provided in an embodiment of the present invention.

[0038] Figure 2 A schematic diagram of spraying antifreeze liquid for coal provided in an embodiment of the present invention.

[0039] Figure 3 This is a scene diagram of the frozen coal on the bottom of the carriage in Test Example 1 using the antifreeze solution for coal provided by the present invention.

[0040] Figure 4 This is a scene picture of the situation in which there is no trace of frozen coal on the side wall after the carriage overturned in test example 1 using the antifreeze liquid for coal provided by the present invention.

[0041] Figure 5 This is a scene picture of the carriage after the train sprayed with the antifreeze for coal provided by the present invention in Test Example 2 overturned.

[0042] Figure 6 This is a scene picture of the carriage situation after the train sprayed with the existing antifreeze provided by the present invention in Test Example 2 overturned.

[0043] Figure 7 This is a scene diagram of the surroundings and bottom of the carriage where the antifreeze for coal provided by the present invention is sprayed in Test Example 2.

[0044] Figure 8 This is a scene diagram of the surroundings and bottom of the vehicle compartment sprayed with the existing antifreeze solution provided by the present invention in Test Example 2. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0047] In a first aspect, the present invention provides a polymer stabilizer, such as Figure 1 As shown, the preparation method of the polymer stabilizer comprises the following steps:

[0048] Mixing water, an emulsifier, vinyl acetate accounting for 1 / 6 to 1 / 4 of the weight of the total vinyl acetate, and an initiator accounting for 1 / 6 to 1 / 4 of the weight of the total initiator, and then stirring and heating to perform a prepolymerization reaction to obtain a first reaction system;

[0049] Add the remaining vinyl acetate and the remaining initiator dropwise to the first reaction system, and continue to stir and react under heat preservation after the addition is completed to obtain a second reaction system;

[0050] Adding glycerol and alkylphenol polyoxyethylene ether into the second reaction system to carry out polymerization reaction to obtain a third reaction system;

[0051] The third reaction system is cooled to room temperature to obtain the polymer stabilizer.

[0052] The present invention provides a polymer stabilizer and further applies it to antifreeze liquid for coal. The polymer stabilizer can be compounded with urea, sodium salts and nanocellulose to produce a good synergistic effect, so that the freezing point is low and the viscosity is high. At the same time, the growth of microorganisms in the system can be inhibited, so that the freezing point and viscosity stability of the entire liquid phase system are greatly improved, and the influence of the environment and the water content in the coal can be basically ignored.

[0053] In some specific embodiments, the weight ratio of the water, the emulsifier, the vinyl acetate, the initiator, the glycerol and the alkylphenol polyoxyethylene ether is (58-65):(0.5-1.8):(30-45):(0.02-0.09):(0.3-2):(0.3-2); the emulsifier includes sodium lauryl sulfate and alkylphenol polyoxyethylene ether; the initiator includes ammonium persulfate; the alkylphenol polyoxyethylene ether includes at least one of alkylphenol polyoxyethylene ether OP-15 and alkylphenol polyoxyethylene ether OP-10.

[0054] In some specific embodiments, the working condition parameters of the prepolymerization reaction include: temperature of 80-90°C, time of 20-40 minutes; the working condition parameters of the heat preservation and stirring reaction include: temperature of 80-90°C, time of 50-70 minutes; the working condition parameters of the polymerization reaction include: temperature of 80-90°C, time of 50-70 minutes; the cooling temperature is 45-55°C.

[0055] In the second aspect, based on the same inventive concept, the present invention provides an antifreeze solution for coal, which comprises the following components in terms of weight percentage:

[0056] 1% to 20% of the polymer stabilizer described in any one of the first aspects, 0.1% to 5% of the nanocellulose compound, 35% to 55% of the urea and sodium salt compound, 0.8% to 5% of the pH regulator, and the balance is water.

[0057] Among them, the above-mentioned polymer stabilizer, the stabilizer component includes vinyl acetate, ammonium persulfate, sodium dodecyl sulfate, glycerol, and alkylphenol polyoxyethylene ether; the above-mentioned nanocellulose mixture is a compound of nanocellulose and nanoxanthan gum; the above-mentioned urea and sodium salt compound is one or more compounds of urea, sodium carbonate, sodium acetate, sodium formate, sodium nitrite, sodium thiosulfate, sodium persulfate, sodium nitrate, and sodium silicate; the above-mentioned pH adjuster is triethanolamine.

[0058] Nanocellulose (ncc): filamentous, purity> 99%, extracted from natural cellulose, compared with conventional cellulose, nanocellulose has higher crystallinity and smaller size, unique structure, large specific surface area, large aspect ratio, strong rigidity, strong surface activity, can be physically and chemically modified to form a variety of excellent performance derivatives. At the same time, its surface is rich in active hydroxyl groups, high aspect ratio, small size, good thermal stability, large surface charge, so that it can be stably dispersed in water, and form a stable space grid structure, with good hydrophilicity and viscosity.

[0059] Nano xanthan gum: double helix structure, nanometer scale, can dissolve high-valent metal ions in water, thereby inhibiting the self-aggregation of the system due to adsorption of cations, and increasing the viscosity of the system on a macro scale.

[0060] Nanocellulose compound (nanocellulose: nanoxanthan gum = mass ratio 1:1-1:3.5): After nanocellulose and nanoxanthan gum are compounded, the active hydroxyl groups on the surface of nanocellulose can form hydrogen bonds with water molecules and nanoxanthan gum. Due to the small volume, large specific surface area, many surface active hydroxyl groups and high degree of dispersion of nanocellulose, a large number of spatial network structures interconnected by hydrogen bonds and van der Waals forces will be formed in the microchlorine antifreeze system containing nanocellulose compound. At the same time, the surface of nanocellulose compound carries a large amount of negative charge. Under the action of electrostatic repulsion, the nanocellulose compound maintains a certain distance and dispersion degree.

[0061] The antifreeze solution for coal provided by the present invention has high economic benefits. Specifically:

[0062] 1. Direct economic benefits

[0063] Calculated based on a 10,000-ton train, each train has 102 carriages, with an inner length × inner width × inner height = 13m × 2.892m × 2.05m. The surface area of ​​a carriage is 102.7532m2, so the coal loss of a train is 102 × 102.7532 × 26 = 272501.49kg, about 272.5 tons. Calculated at 800 yuan / ton, the loss of a train is 218,000 yuan.

[0064] The spraying amount of antifreeze for coal is 0.620kg / m2, plus the spraying loss coefficient of 0.31, the spraying amount is 0.93kg / m2. A train needs 102×102.7532×0.93=9747.17kg of antifreeze, which is about 9.747 tons. The spraying amount is small.

[0065] 2. Indirect economic benefits

[0066] Since coal antifreeze has the characteristics of low freezing point, good stability, strong adsorption, no corrosion to metal and rubber, non-volatile, non-toxic and non-irritating odor, it can generate indirect economic benefits in many aspects:

[0067] (1) In the past, methanol was added to antifreeze, which was highly volatile and operators working in the workshop for a long time were prone to occupational diseases.

[0068] (2) Effectively reduce the damage of antifreeze to transportation, storage, and spraying equipment (mainly the impact of antifreeze on metal equipment, accessories, and tire life), reducing equipment wear and tear.

[0069] (3) The improvement of antifreeze formula has optimized the production process, reduced the process and operators, and reduced production costs.

[0070] (4) Effectively avoid the expenditure of labor costs for cleaning coal cars, road occupation fees and other fines, thereby reducing costs.

[0071] (5) The adverse impact on downstream chemical coal consumption is minimized, increasing the profits of downstream companies.

[0072] In some specific embodiments, the antifreeze solution for coal includes the following components by weight percentage:

[0073] 9% polymer stabilizer, 0.5% nanocellulose compound, 50% urea and sodium salt compound, 3% pH adjuster, and the balance is water.

[0074] In some specific embodiments, the nanocellulose compound is obtained by compounding nanocellulose and nano-xanthan gum; the weight ratio of the nanocellulose to the nano-xanthan gum is 1:(1-3.5).

[0075] In some specific embodiments, the urea and sodium salt compound is a compound of urea and sodium salt in a weight ratio of (15-30):(65-85); the sodium salt includes at least one of sodium carbonate, sodium acetate, sodium formate, sodium nitrite, sodium thiosulfate, sodium persulfate, sodium nitrate, and sodium silicate; and the pH adjuster includes triethanolamine.

[0076] In some specific embodiments, the performance index parameters of the coal antifreeze liquid include: Appearance: colorless or milky white liquid; Density: 1.100-1.500 (g / cm 3 ); viscosity, freezing point stability ≥ 30 days; freezing point: -50 ℃ ~ -60 ℃, chlorine content: ≤80mg / kg, calcium content: ≤5wt%, viscosity at 20 ℃: 30 ~ 60mPa·s, pH value: 6.5 ~ 9.5.

[0077] In a third aspect, based on the same inventive concept, the present invention provides a method for preparing the antifreeze solution for coal according to any one of the second aspects, the preparation method comprising the following steps:

[0078] The water, urea and sodium salt compound are stirred and mixed, and then the nanocellulose mixture is added and stirred and mixed to obtain a first mixture;

[0079] The remaining components in the antifreeze liquid for coal are added to the first mixed material, and the mixture is stirred and mixed to obtain the antifreeze liquid for coal.

[0080] The preparation method of the antifreeze liquid for coal provided by the present invention is simple to operate, does not require additional specific equipment, and is suitable for batch industrial production.

[0081] It should be noted that the component raw materials involved in the antifreeze for coal and the preparation method thereof provided in the embodiments of the present invention, unless otherwise specified or specified, can be directly commercially available products or homemade using existing public preparation methods; at the same time, the steps and parameters involved, unless otherwise specified or specified, can be carried out according to the existing processing technology of antifreeze for coal or directly using existing equipment, and the present invention document will not describe them one by one.

[0082] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0083] Example 1

[0084] This example provides a polymer stabilizer, and the preparation method of the polymer stabilizer comprises the following steps:

[0085] Mixing water, an emulsifier, vinyl acetate accounting for 1 / 5 of the weight ratio of the total vinyl acetate, and an initiator accounting for 1 / 5 of the weight ratio of the total initiator, and then stirring and heating to perform a prepolymerization reaction to obtain a first reaction system;

[0086] Add the remaining vinyl acetate and the remaining initiator dropwise to the first reaction system, and continue to stir and react under heat preservation after the addition is completed to obtain a second reaction system;

[0087] Adding glycerol and alkylphenol polyoxyethylene ether into the second reaction system to carry out polymerization reaction to obtain a third reaction system;

[0088] Cooling the third reaction system to room temperature to obtain the polymer stabilizer;

[0089] Wherein, the weight ratio of the water, the emulsifier, the vinyl acetate, the initiator, the glycerol and the alkylphenol polyoxyethylene ether is 608:13:364:0.85:6:6; the emulsifier is sodium dodecyl sulfate; the initiator is ammonium persulfate, and the alkylphenol polyoxyethylene ether is alkylphenol polyoxyethylene ether OP-10; the working condition parameters of the prepolymerization reaction include: temperature of 82°C and time of 30 minutes; the working condition parameters of the heat preservation and stirring reaction include: temperature of 82°C and time of 60 minutes; the working condition parameters of the polymerization reaction include: temperature of 90°C and time of 60 minutes; the cooling temperature is 50°C.

[0090] Example 2

[0091] This example provides an antifreeze solution for coal, which includes the following components by weight percentage: 7.74% polymer stabilizer, 0.12% nanocellulose compound, 42.56% urea and sodium salt compound, 1.21% pH regulator, and the balance is water;

[0092] Among them, the polymer stabilizer is obtained in Example 1; the nanocellulose compound is obtained by compounding nanocellulose and nano xanthan gum, and the weight ratio of the nanocellulose and the nano xanthan gum is 1:1; the urea and sodium salt compound is compounded by urea and sodium salt in a weight ratio of 20:68, and the sodium salt is composed of sodium acetate and sodium formate in a weight ratio of 40:28; the pH adjuster is triethanolamine.

[0093] The preparation method of the above-mentioned antifreeze for coal specifically includes the following process: add 100kg of water, then add 28kg of sodium formate, 20kg of urea, 40kg of sodium acetate, and 0.25kg of nanocellulose composite material, stir for 1h to completely dissolve, then add 16kg of synthesized polymer stabilizer and 2.5kg of triethanolamine, mix well, and then you can get the antifreeze for coal.

[0094] After testing, the physical and chemical properties of the coal antifreeze obtained in this example include: density: 1.215g / cm 3 , viscosity: 32mPa·s freezing point -51℃, pH: 6.7, chlorine content 65mg / kg, calcium content: ≤5%, viscosity and freezing point stability 35 days.

[0095] Example 3

[0096] This example provides an antifreeze solution for coal, which includes the following components by weight percentage: 9% polymer stabilizer, 0.5% nanocellulose compound, 50% urea and sodium salt compound, 3% pH regulator, and the balance is water;

[0097] Among them, the polymer stabilizer is obtained in Example 1; the nanocellulose compound is obtained by compounding nanocellulose and nano xanthan gum, and the weight ratio of the nanocellulose and the nano xanthan gum is 1:3; the urea and sodium salt compound is compounded by urea and sodium salt in a weight ratio of 28:72, and the sodium salt is composed of sodium acetate and sodium nitrite in a weight ratio of 36:36; the pH adjuster is triethanolamine.

[0098] The preparation method of the above-mentioned antifreeze for coal specifically includes the following process: add 75kg of water, then add 36kg of sodium nitrite, 36kg of sodium acetate, 28kg of urea, and 1kg of nanocellulose composite material, stir for 1h until completely dissolved, then add 18kg of synthesized polymer stabilizer and 6kg of triethanolamine, mix well, and then you can get the antifreeze for coal.

[0099] After testing, the physical and chemical properties of the coal antifreeze obtained in this example include: density: 1.232g / cm 3 , viscosity: 53mPa·s freezing point -56℃, pH: 7.0, chlorine content 62mg / kg, calcium content: ≤5%, viscosity and freezing point stability 90 days.

[0100] Example 4

[0101] This example provides an antifreeze solution for coal, which includes the following components by weight percentage: 6% polymer stabilizer, 0.3% nanocellulose compound, 55% urea and sodium salt compound, 4.5% pH regulator, and the balance is water;

[0102] Among them, the polymer stabilizer is obtained in Example 1; the nanocellulose compound is obtained by compounding nanocellulose and nano xanthan gum, and the weight ratio of the nanocellulose and the nano xanthan gum is 1:2; the urea and sodium salt compound is compounded by urea and sodium salt in a weight ratio of 14:41, and the sodium salt is composed of sodium nitrate and sodium acetate in a weight ratio of 17:24; the pH adjuster is triethanolamine.

[0103] The preparation method of the above-mentioned antifreeze for coal specifically includes the following process: add 342kg of water, then add 170kg of sodium nitrate, 240kg of sodium acetate, 140kg of urea, and 3kg of nanocellulose composite material, stir for 1h until completely dissolved, then add 60kg of synthesized polymer stabilizer and 45kg of triethanolamine, mix well, and then the antifreeze for coal can be obtained.

[0104] After testing, the physical and chemical properties of the coal antifreeze obtained in this example include: density: 1.212g / cm 3 , viscosity: 41mPa·s freezing point -50℃, pH: 8.5, chlorine content 70mg / kg, calcium content: ≤5%, viscosity and freezing point stability 55 days.

[0105] Example 5

[0106] This example provides an antifreeze solution for coal, which includes the following components by weight percentage: 11.6% polymer stabilizer, 0.48% nanocellulose compound, 45.41% urea and sodium salt compound, 2.90% pH regulator, and the balance is water;

[0107] Among them, the polymer stabilizer is obtained in Example 1; the nanocellulose compound is obtained by compounding nanocellulose and nano xanthan gum, and the weight ratio of the nanocellulose and the nano xanthan gum is 1:1; the urea and sodium salt compound is compounded by urea and sodium salt in a weight ratio of 26:68, and the sodium salt is composed of sodium nitrite and sodium acetate in a weight ratio of 34:34; the pH adjuster is triethanolamine.

[0108] The preparation method of the above-mentioned antifreeze for coal specifically includes the following process: add 82kg of water, then add 34kg of sodium nitrite, 34kg of sodium acetate, 26kg of urea, and 1kg of nanocellulose composite material, stir for 1h until completely dissolved, then add 24kg of synthesized polymer stabilizer and 6kg of triethanolamine, mix well, and then you can get the antifreeze for coal.

[0109] After testing, the physical and chemical properties of the coal antifreeze obtained in this example include: density: 1.203g / cm 3, viscosity: 35mPa·s freezing point -52℃, pH: 6.9, chlorine content 58mg / kg, calcium content: ≤5%, viscosity and freezing point stability 82 days.

[0110] Comparative Example 1

[0111] This example provides an antifreeze liquid for coal and a preparation method thereof, which is different from Example 3 only in that the weight ratio of the nano-cellulose to the nano-xanthan gum is 3.5:1; the remaining steps and parameters are the same.

[0112] After testing, the physical and chemical properties of the coal antifreeze obtained in this example include: density: 1.208g / cm 3 , viscosity: 15mPa·s freezing point -50℃, pH: 7.2, chlorine content 61mg / kg, calcium content: ≤5%, viscosity and freezing point stability 18 days.

[0113] Comparative Example 2

[0114] This example provides an antifreeze liquid for coal and a preparation method thereof, which differs from Example 3 only in that: the polymer stabilizer is prepared by the following preparation method: water, an emulsifier, vinyl acetate and an initiator are mixed, and then stirred and heated to carry out a prepolymerization reaction to obtain a first reaction system; the first reaction system is cooled to room temperature to obtain the polymer stabilizer; the working condition parameters of the prepolymerization reaction include: temperature of 85°C and time of 150 minutes; the remaining steps and parameters are the same.

[0115] After testing, the physical and chemical properties of the coal antifreeze obtained in this example include: density: 1.208g / cm 3 , viscosity: 45mPa·s freezing point -35℃, pH: 7.2, chlorine content 61mg / kg, calcium content: ≤5%, viscosity and freezing point stability for 7 days.

[0116] Comparative Example 3

[0117] This example provides an antifreeze liquid for coal and a preparation method thereof, which differs from Example 3 only in that: the urea and sodium salt compound is composed of urea and sodium salt in a weight ratio of 72:30, and the sodium salt is composed of sodium acetate and sodium nitrite in a weight ratio of 36:36; the remaining steps and parameters are the same.

[0118] After testing, the physical and chemical properties of the coal antifreeze obtained in this example include: density: 1.200g / cm 3 , viscosity: 52mPa·s freezing point -28℃, pH: 7.2, chlorine content 60mg / kg, calcium content: ≤5%, viscosity and freezing point stability 41 days.

[0119] Application Example 1

[0120] The antifreeze solution for coal obtained in Example 3 is applied to the actual transportation of coal. The schematic diagram of spraying the antifreeze solution for coal is as follows: Figure 2 As shown, the specific process includes: discharging the prepared and stirred antifreeze for coal into the liquid storage tank, setting the spraying flow of the central control spraying system, clicking the operating surface valve, lowering the spraying rack after the car body is in place, and starting to spray the antifreeze for coal.

[0121] On January 13 and 14, 2022, three Pingshuo coal-carrying trains were sprayed on the sides of the carriages and sent to Qinhuangdao Port or Jingtang Port. The trains were unloaded and the condition was observed on site. After being transported to the destination, the frozen coal on the sides of the carriages was observed. It can be seen that there is no trace of frozen coal in the carriage, especially on the side walls of the carriages, and the antifreeze liquid has good adsorption performance. The on-site picture of the frozen coal on the bottom of the carriage is as follows Figure 3 shown.

[0122] Application Example 2

[0123] The coal antifreeze obtained in Example 3 and the existing antifreeze (specifically calcium chloride dihydrate aqueous solution, the composition and dosage relationship of which is: 40% calcium chloride dihydrate aqueous solution) were applied to the actual transportation of coal, and the specific test data are shown in Table 1. Figure 5 , Figure 6 , Figure 7 and Figure 8 As shown, Figure 5 It shows that after the train sprayed with the antifreeze for coal provided by the present invention is turned over, there is no sticking in the carriage, and there is no frozen coal around the wall, and it is poured out completely, which shows that the antifreeze has good adsorption performance. Figure 6 It shows that after the train sprayed with existing antifreeze liquid overturned, there was obvious frozen coal sticking to the walls of the carriage, indicating that the adsorption performance of the existing antifreeze liquid was poor. Figure 7 It shows that: there is no frozen coal sticking around and on the bottom of the carriage sprayed with the antifreeze for coal provided by the present invention, and the coal can be poured out completely. Figure 8 The results show that the walls and bottom of the carriages sprayed with the existing antifreeze liquid have varying degrees of frozen coal sticking to them.

[0124] Table 1

[0125] Spraying category Train No. Gross weight of train / t Tare weight after unloading / t Net weight / t Standard net weight 8160 tons Antifreeze for low-chlorine coal 872069 10348 2179 8169 Profit 9 tons Existing antifreeze 872085 10206 2374 7832 Loss of 328 tons

[0126] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0127] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A polymer stabilizer, characterized in that The preparation method of the polymer stabilizer comprises the following steps: Mixing water, an emulsifier, vinyl acetate accounting for 1 / 6 to 1 / 4 of the weight of the total vinyl acetate, and an initiator accounting for 1 / 6 to 1 / 4 of the weight of the total initiator, and then stirring and heating to perform a prepolymerization reaction to obtain a first reaction system; Add the remaining vinyl acetate and the remaining initiator dropwise to the first reaction system, and continue to stir and react at room temperature after the addition is completed to obtain a second reaction system; Adding glycerol and alkylphenol polyoxyethylene ether into the second reaction system to carry out polymerization reaction to obtain a third reaction system; The third reaction system is cooled to room temperature to obtain the polymer stabilizer.

2. The polymer stabilizer according to claim 1, characterized in that The weight ratio of the water, the emulsifier, the vinyl acetate, the initiator, the glycerol and the alkylphenol polyoxyethylene ether is (58-65):(0.5-1.8):(30-45):(0.02-0.09):(0.3-2):(0.3-2); the emulsifier includes sodium lauryl sulfate and alkylphenol polyoxyethylene ether; the initiator includes ammonium persulfate; the alkylphenol polyoxyethylene ether includes at least one of alkylphenol polyoxyethylene ether OP-15 and alkylphenol polyoxyethylene ether OP-10.

3. The polymer stabilizer according to claim 1, characterized in that The working condition parameters of the prepolymerization reaction include: temperature of 80-90°C and time of 20-40 minutes; the working condition parameters of the heat preservation and stirring reaction include: temperature of 80-90°C and time of 50-70 minutes; the working condition parameters of the polymerization reaction include: temperature of 80-90°C and time of 50-70 minutes.

4. A coal antifreeze solution, characterized in that: The antifreeze solution for coal comprises the following components in weight percentage: 1% to 20% of the polymer stabilizer according to any one of claims 1 to 3, 0.1% to 5% of the nanocellulose compound, 35% to 55% of the urea and sodium salt compound, 0.8% to 5% of the pH regulator, and the balance is water.

5. The antifreeze liquid for coal according to claim 4, characterized in that: The antifreeze solution for coal comprises the following components in weight percentage: 9% polymer stabilizer, 0.5% nanocellulose compound, 50% urea and sodium salt compound, 3% pH regulator, and the balance is water.

6. The antifreeze solution for coal according to claim 4, characterized in that: The nanocellulose compound is obtained by compounding nanocellulose and nanoxanthan gum; the weight ratio of the nanocellulose to the nanoxanthan gum is 1:(1-3.5).

7. The antifreeze liquid for coal according to claim 4, characterized in that: The urea and sodium salt compound is prepared by compounding urea and sodium salt in a weight ratio of (15-30):(65-85); the sodium salt comprises at least one of sodium carbonate, sodium acetate, sodium formate, sodium nitrite, sodium thiosulfate, sodium persulfate, sodium nitrate and sodium silicate; and the pH regulator comprises triethanolamine.

8. The antifreeze liquid for coal according to claim 4, characterized in that: The performance index parameters of the coal antifreeze liquid include: freezing point: -50°C to -60°C, chlorine content: ≤80mg / kg, calcium content: ≤5wt%, viscosity at 20°C: 30 to 60mPa·s, and pH value: 6.5 to 9.

5.

9. A method for preparing the antifreeze solution for coal according to any one of claims 4 to 8, characterized in that: The preparation method comprises the following steps: The water, urea and sodium salt compound are stirred and mixed, and then the nanocellulose mixture is added and stirred and mixed to obtain a first mixture; The remaining components in the antifreeze liquid for coal are added to the first mixed material, and the mixture is stirred and mixed to obtain the antifreeze liquid for coal.